Investigation of the Possibility of Using Microspectrometers Based on CMOS Photodiode Arrays in Small-Sized Devices for Optical Diagnostics - Oleksandra Hotra; Vladimir Firago; Nikolay Levkovich; Konstantin Shuliko (Sensors, 2022)
The article considers the potential applicability of C12880MA and C11708MA Hamamatsu microspectrometers, which are characterized by an extremely compact design, occupying a small volume of several cubic centimeters, in portable spectrometric equipment with spatial resolution for monitoring the optical properties of condensed scattering media. The development of methods for determining the reduced scattering and absorption spectral coefficients of radiation from various scattering materials and products allows us to speak about the possibility of real-time control of the volume concentration of optically active components included in them, for example, fat and water in dairy products. For this, it is necessary to provide sufficiently accurate spectra of diffusely reflected broadband light radiation at different distances between the points of radiation entrance and registration. The aim of the manuscript is to assess the possibility of using the considered microspectrometers in compact devices for optical diagnostics and control of the optical properties of condensed scattering media. The features of the connection diagram of these microspectrometers and the necessary methods for correcting the initially obtained spectral dependencies of diffusive reflection, which will be of interest to developers of spectral diagnostic equipment, are considered in detail. The need to eliminate the influence of the inhomogeneity of dark counts of a CMOS photodiode array is shown. The hardware functions of the C12880MA and C11708MA Hamammatsu microspectrometers, as well as the AvaSpec 2048L fiber-optic spectrometer, were experimentally measured and compared. Methods for correcting the nonlinearity of their reading scales and light characteristics, as well as improving their equivalent spectral resolution using digital Wiener filtering, are described. It is shown that the equivalent spectral resolution of C12880MA and C11708MA microspectrometers can be improved by about 40% when recording smooth spectra, subject to the condition that the resulting side oscillations are small. It is pointed out that in order to reduce the level of side oscillations in the corrected spectra with improved resolution, it is necessary to ensure the smoothness of the original spectra and a good signal-to-noise ratio. A conclusion is made about the possibility of using the considered microspectrometers in portable spectrometric equipment with careful consideration of their characteristics, the features of their switching circuit, and the necessary software.